2021
DOI: 10.2478/dim-2020-0050
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Academic Social Networking Sites in Scholarly Communication: Scoping Review

Abstract: This research provides a systematic analysis of 115 previous literatures on the use of academic social networking sites (ASNs) in scholarly communication. Previous research on the subject has mainly taken a disciplinary and user perspective. This research conceptualizes the use of ASNs in scholarly communication in the space between social interactions and the technologies themselves. Keyword analysis and scoping review approaches have been used to analyze the comprehensive literature in the field. The study f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 113 publications
0
6
0
Order By: Relevance
“…Although often identified as a separate motivating factor, accessibility is very closely interrelated to altruistic motives and reciprocity (and is, by far, the most often cited reason for self-archiving). Researchers aim to increase the accessibility of their work, and by making it available in institutional and subject repositories or through websites and social networking sites, researchers believe that they can reach more people and also make their work more easily discoverable than through subscription journals alone (Creaser et al, 2010;Baro et al, 2018;Lee et al, 2019;Hailu & Wu, 2021). Lee et al (2020) classified psychology with other "soft pure" sciences (such as sociology) in their study of disciplinary differences in motivations for selfarchiving on ResearchGate and found that this group was more highly motivated by accessibility, as well as personal and professional benefits, than the hard sciences, although they did not identify significant differences in motivations between pure and applied groups.…”
Section: Motivations For Self-archivingmentioning
confidence: 99%
“…Although often identified as a separate motivating factor, accessibility is very closely interrelated to altruistic motives and reciprocity (and is, by far, the most often cited reason for self-archiving). Researchers aim to increase the accessibility of their work, and by making it available in institutional and subject repositories or through websites and social networking sites, researchers believe that they can reach more people and also make their work more easily discoverable than through subscription journals alone (Creaser et al, 2010;Baro et al, 2018;Lee et al, 2019;Hailu & Wu, 2021). Lee et al (2020) classified psychology with other "soft pure" sciences (such as sociology) in their study of disciplinary differences in motivations for selfarchiving on ResearchGate and found that this group was more highly motivated by accessibility, as well as personal and professional benefits, than the hard sciences, although they did not identify significant differences in motivations between pure and applied groups.…”
Section: Motivations For Self-archivingmentioning
confidence: 99%
“…, 2022). The success of ASNSs can be partly attributed to a large number of regular users communicating and academic resources shared, such as papers, data and projects shared on such sites (Hailu and Wu, 2021; Zheng et al. , 2019).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…, 2021). Sustained information seeking reflects users' long-term engagement with online scholarly communication, which is also vital to the development and sustainability of ASNSs (Hailu and Wu, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations